PERAMALAN CURAH HUJAN DAN LUAS SERANGAN ORGANISME PENGGANGGU TANAMAN DI KABUPATEN BOGOR - Faradiba Faradiba (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The agricultural sector is still a reliable sector in Indonesia. The most favored commodity from the agricultural sector is rice. Rice production is strongly influenced by Pest Attack (OPT) and rainfall intensity. The life cycle of OPT in rice is also affected by the intensity of rainfall. This study aims to determine the forecasting of rainfall and the extent of OPT for 2018. The location of the study was taken in Bogor Regency, West Java Province. This study uses secondary data in the form of rainfall data and extensive data on pest attacks in 2006-2017. In this study using the Exponential Smoothing Method and the level of accuracy of forecasting results using Mean Square Error (MSE) and Mean Absolut Deviation (MAD). Forecasting Results Rainfall and the extent of OPT attacks for 2018 were obtained 313.20 mm and 1,967 m2 respectively. Rainfall rates in 2018 were categorized as normal.Keyword: forecasting, rainfall, pest attack, Exponential Smoothing.